Ionic Response and Sorghum Production under Water and Saline Stress in a Semi-Arid Environment - Rodrigo Rafael da Silva; José Francismar de Medeiros; Gabriela Carvalho Maia de Queiroz; Leonardo Vieira de Sousa; Maria Vanessa Pires de Souza; Milena de Almeida Bastos do Nascimento; Francimar Maik da Silva Morais; Renan Ferreira da Nóbrega; Lucas Melo e Silva; Fagner Nogueira Ferreira; Maria Isabela Batista Clemente; Carla Jamile Xavier Cordeiro; et al. (Agriculture, 2023)
The increase in water demand in regions with limited good-quality water resources makes it necessary to study the effect of low-quality water on plant metabolism. Therefore, the objective of this study was to evaluate the effect of water and salt stress on the levels of mineral elements and accumulation of toxic elements Na+ and Cl− in the leaves and their consequences on the production variables of the sorghum cultivar IPA SF-15. The design adopted was randomized blocks in a factorial scheme (4 × 4), with four salt concentrations (1.5; 3.0; 4.5, and 6.0 dS m−1) and four irrigation depths (51.3; 70.6; 90.0, and 118.4% of crop evapotranspiration ETc) in three repetitions. To obtain nutrient, sodium, and chlorine contents in the leaf, we collected the diagnosis leaf from six plants per plot. For production data, we performed two harvests at 76 and 95 days after planting (silage point and for sucrose extraction). We evaluated the dry mass, fresh mass yield, and total dry mass for the two cutting periods and applied the F-test at the 5% significance level. There was an effect of water stress but not saline, making it possible to use saline water for sorghum irrigation. As for the toxicity of ions, the plant showed tolerance behavior to Na+ and Cl− ions. The grain filling phase was more sensitive than the final phase of the crop cycle.